2020
DOI: 10.1111/teth.12568
|View full text |Cite
|
Sign up to set email alerts
|

Learning about Islam and Muslims online: Reflections on the design and delivery of a massive open online course (MOOC) 2014–2019

Abstract: This article evaluates the design, delivery, and main outcomes of Cardiff University's first “Massive Open Online Course” (MOOC) entitled “Muslims in Britain: Changes and Challenges,” delivered to over 20,899 international learners between 2014 and 2019. I explore the design principles underpinning the course and offer a detailed quantitative overview of our learner‐base. The paper examines the experience of course delivery, as well as providing an evaluation of the outcomes arising from the course in the shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Results of this review revealed that micro-credentials provided students with a wide range of benefits associated with study and career progression that align with the Tomlinson (2017)'s model regarding the development of different forms of employability capitals. These were evidence within the literature relative to human (Alt, 2021;Newby & Cheng, 2020), social (Anderson et al, 2020;Gilliat-Ray, 2020), cultural (Dayton et al, 2018;Laverie et al, 2020), identity (Cowley et al, 2021;Humphrey Jr et al, 2021), and psychological capital (Boo & Kim, 2020;Laverie et al, 2020).…”
Section: A 'Non-zero-sum Game'mentioning
confidence: 67%
See 2 more Smart Citations
“…Results of this review revealed that micro-credentials provided students with a wide range of benefits associated with study and career progression that align with the Tomlinson (2017)'s model regarding the development of different forms of employability capitals. These were evidence within the literature relative to human (Alt, 2021;Newby & Cheng, 2020), social (Anderson et al, 2020;Gilliat-Ray, 2020), cultural (Dayton et al, 2018;Laverie et al, 2020), identity (Cowley et al, 2021;Humphrey Jr et al, 2021), and psychological capital (Boo & Kim, 2020;Laverie et al, 2020).…”
Section: A 'Non-zero-sum Game'mentioning
confidence: 67%
“…This review also identified that low quality course design, content, and instructions were the most frequently reported challenge facing students when studying micro-credentials (e.g., Cowley et al, 2021;Gilliat-Ray, 2020). This finding mirrored the difficulties that higher education providers encountered when developing and implementing microcredentials.…”
Section: No Micro Task For Students or Higher Education Providersmentioning
confidence: 81%
See 1 more Smart Citation